Answer: 5(x-2) + 3 [aka 5x - 7, whichever form your computer accepts these both mean the same]
Steps
Solve for the inverse function of
f(x)=((x-3)/5)+2
First one should replace the variables so
that f(x)=((x-3)/5)+2 becomes:
x=((y-3)/5)+2 (this isn’t necessary, it just makes it easier for those to remember the variable they are looking for when first learning about inverses) —> regardless, we are searching for y.
So doing regular algebra, we get:
x=((y-3)/5)+2
x-2=((y-3)/5)
5(x-2)=y-3
5(x-2)+3=y
Thus, the inverse: f(x)^-1 = 5x-7